Removal of Toxic Lead Ions in Presence of Cationic Surfactants - Darweesh, Mona; Ahmed, A.M. (Asian Journal of Chemistry, 2013)
The removal of toxic Pb2+ from waste water by cementation on rotating zinc cylinder takes place in absence and in presence of cationic surfactants as cetyl trimethylammonium bromide (CTAB) and cetyl pyridinium bromide (CPYB). The rate of removal of Pb2+ was studied under different conditions of rotation speed, initial Pb2+ concentration, temperature and different types of cationic surfactants. It was found that, the rate of removal of Pb2+ increases with increasing rotation speed (rpm) and temperatures. The presence of surfactants was found to decrease the rate of cementation. The decrease in the rate of cementation was ranged from 29 to 78 % depending on the type of surfactants and its concentration. Thermodynamic parameters DG*, DH* and DS* were calculated.